(untitled) (Research, Society and Development, 2021)
This is a report of experiences of teaching-service-community integration, of a tutorial group of the Education for Health Work Program (Pet-Saúde), whose thematic axis was Interprofessional Education (IPE), carried out between April 2019 and March 2021. The project was carried out in partnership between the Federal University and the Health Secretariat of a municipality in the interior of Maranhão with theme Integral Health of the LGBTQIA+ Population, consisting of academics from three courses (Physical Education, Nursing, and Medicine), preceptors from Primary Health Care, coordinator, and faculty tutors. During the two years of activities, the group has been able to carry out studies related to the themes of IPE and LGBTQIA+ health, with situational diagnosis and recognition of the territory in relation to the attention dedicated to this population. Promoted discussions about collaborative skills and the challenges for the implementation of the National Policy of Integral Health of the LGBTQIA+ Population. Conducted research, scientific papers, and preparation of articles. In addition to conducting IPE through remote teaching during the pandemic, supporting the community and professionals in coping with COVID-19. We conclude with the experience of the PET LGBTQIA+ Health group, for the work developed, that it was possible to leave a legacy for the university and the health system, for having allowed approximations that were previously unthought of among courses, students, teachers, and preceptors, and for having encouraged the implementation of discussions and reflections on collaborative practices and health specificities of the LGBTQIA+ population, never done before with such intensity.